China trade with belt and road countries: the role and impact of institutions. Issue 1 (2nd January 2022) - Bakhsh, Satar; Yin, He; Shabir, Mohsin; Ali, Kishwar
ABSTRACT: This article investigates the impact of institutional quality on China's trade with belt and road economies by testing the augmented gravity model framework. Our empirical analysis is based on 16 years of balanced panel data of 65 belt and road economies. We use the instrumental variable estimator developed for a panel data model to address the potential endogeneity issue. We distinguish the vital role of institutions in trading partner countries in shaping this result. Our outcomes outline an interesting story about the association between institutional quality and China's export to and import from belt and road countries. We find that the weaker voice and accountability and political stability in B&R countries negatively affect China exports, while China import from B&R economies shows a statistically positive effect of institutions. Our findings are robust to employs a panel pseudo-maximum likelihood (PPML) estimation method. As part of wider trade integration, we conclude that the B&R countries should strengthen their institutions. The results of this study have several implications for policymakers.